Promoting Youth Opportunities and Participation in Morocco - La Cava, Gloria; Vishwanath, Tara; Morgandi, Matteo; Serajuddin, Umar; Ivanic, Maros; Jillson, Irene (World Bank, Washington, DC, 2013)
This quick note is based on the report of the same name which was prepared just prior to the Arab Spring. The study anticipates the demands for social and economic inclusion articulated by Moroccan young people, especially February 2011. Since then, these demands have been amplified and reached a new level of urgency. This study adopts a mixed method approach combining an innovative quantitative instrument with qualitative and institutional analysis. The goal is to provide policy makers with a nuanced analysis of barriers to employment and active civic participation encountered by young people aged 15 to 29 years so as to tailor youth interventions more effectively. It identifies a wide range of recommendations available to support youth-inclusive activities and policies, and a roadmap for integrated youth investments.